MOTIVASI BERAFILIASI SISWA ETNIS TIONGHOA DI SMA NEGERI 1 TEBAS - Aan Khosihan (Jurnal Analisa Sosiologi, 2016)
The existence of students with chinese ethnic background that is still very small in number in public schools is still a big question mark in education in Kecamatan Tebas. As the second most populous population after Malay, Chinese people prefer to send their children to a private school where their students are dominated by Chinese ethnics. However, the presence of ethnic Chinese students in a small number of public schools is an interesting thing to look at. This study aims to reveal the behavior and supporting factors that make Chinese students choose to stay in the country. Using the David McClelland needs theory approach as well as the use of qualitative methods with primary data collection of observations and interviews. In this study, the researcher took the main informants, which amounted to three people, consisting of one tenth grader, one at eleven class student of IPA, and one at eleven class student of IPS. the researcher successfully identified ten student behaviors that showed motivation of affiliation and two factors supporting the high motivation of affiliated Chinese students in SMA Negeri 1 Tebas.Keywords: Students of Ethnic Chinese, Motivation of Affiliation, Affiliated Behavior, Affiliated Factors. AbstrakKeberadaan siswa dengan latar belakang etnis tionghoa yang masih sangat sedikit jumlahnya di sekolah negeri masih menjadi tanda tanya besar dalam pendidikan di kecamatan tebas. Sebagai penduduk dengan jumlah terbanyak kedua setelah etnis melayu, masyarakat tionghoa lebih memilih untuk menyekolahkan anak mereka disekolah swasta yang para siswanya didominasi oleh kalangan etns Tionghoa. Namun, keberadaan siswa etnis tionghoa pada sekolah negeri yang jumlahnya sedikit menjadi hal yang menarik untuk diteliti. Penelitian ini bertujuan untuk mengungkap perilaku dan faktor pendukung yang membuat siswa etnis tionghoa memilih bertahan disekolah negeri. Dengan menggunakan pendekatan teori kebutuhan David McClelland serta penggunaan metode kualitatif dengan pengumpulan data utama berupa observasi dan wawancara. Dalam penelitian ini, peneliti mengambil informan utama yang berjumlah tiga orang, terdiri dari satu orang siswa kelas sepuluh, satu orang siswa kelas sebelas IPA, dan satu orang siswa kelas sebelas IPS. peneliti berhasil mengidentifikasi sepuluh perilaku siswa yang menunjukkan motivasi berafiliasi dan tiga faktor pendukung tingginya motivasi berafiliasi siswa etnis Tionghoa di SMA Negeri 1 Tebas.Kata Kunci: Siswa Etnis Tionghoa, Motivasi Berafiliasi, Perilaku Berafiliasi, Faktor Berafiliasi.